Legal Politics of Establishing a Health Bill with the Omnibus Law Method - Sofyan Iskandar (IHSA Institute, 2023)
Omnibus law is a new method of changing a legal product in Indonesia. Likewise in regulations in the health sector. The government, through a body that does have the authority to prepare legal products, decided to change legal products in the health sector with the Omnibus law method. There will be at least 15 health law products revamped in the 2023 legislation program in the health sector. Over time, various polemics in the formation of the Health Bill with omnibus law turned out to trigger polemics in the community, especially for related parties such as the health worker profession that exists in Indonesia. This study aims to analyze the politics of law in the formation of the Health Bill using the omnibus law method. The type of research used in this research is normative legal research. The approach used is a statutory and conceptual approach. The results of the study that the direction of legal politics will be closely related to health. Health development is directed at increasing the awareness, willingness, and ability to live a healthy life for everyone in order to realize the highest degree of public health, as an investment for the development of socially and economically productive Human Resources (HR). Then, the legal product of the Health Bill with omnibus law is directed to the fulfillment of the right to health as an integral part of the existence of human rights where the state has an obligation to fulfill and protect the right to health.